Shawn O'Brien: Better off Dead - Book 3 Book 3 - Johnstone, William W.; Johnstone, J. A. (New York, New York : Kensington Publishing Corp., 2016)
Shawn OBrien looks for a missing boy in the Abaddon Cannon Foundry where men are employed as slaves.
Keywords: Missing persons -- Fiction; Texas -- Fiction